1985
DOI: 10.1021/bi00335a011
|View full text |Cite
|
Sign up to set email alerts
|

Refolding a disulfide dimer of cytochrome c

Abstract: A covalent dimer of Saccharomyces cerevisiae iso-1 cytochrome c is stabilized by an interchain disulfide bond involving the cysteine residue penultimate to the C-terminus. The individual chains in the dimer appear to retain the tertiary structural features characteristic for monomeric cytochrome c albeit with some perturbation. The dimer is reversibly denatured by heat, urea, or guanidine hydrochloride in a single cooperative transition whose midpoint is less than that of the monomeric protein. The kinetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…The results of these studies on the acetamide-derivatized monomer of iso-1 cytochrome c clearly show that protein conformations intermediate between monomer and dimer forms are possible, depending on the polarity and charge of the modifying group. Such a conclusion is consistent with results of protease digestion and denaturation studies of Montonaga et al (1965b) and Bryant et al (1985) performed on the sulfiteand iodoacetate-derivatized monomer of iso-1 cytochrome c. More detailed analyses of the structural alterations induced by Cys-102 modification of iso-1 ferricytochrome c must await characterization of the protein derivatives by X-ray diffraction or multidimensional NMR methods.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The results of these studies on the acetamide-derivatized monomer of iso-1 cytochrome c clearly show that protein conformations intermediate between monomer and dimer forms are possible, depending on the polarity and charge of the modifying group. Such a conclusion is consistent with results of protease digestion and denaturation studies of Montonaga et al (1965b) and Bryant et al (1985) performed on the sulfiteand iodoacetate-derivatized monomer of iso-1 cytochrome c. More detailed analyses of the structural alterations induced by Cys-102 modification of iso-1 ferricytochrome c must await characterization of the protein derivatives by X-ray diffraction or multidimensional NMR methods.…”
Section: Discussionsupporting
confidence: 78%
“…3). Studies at higher temperatures were not pursued because Bryant et al (1985) have reported that the heat denaturation midpoint temperature of the disulfide dimer of iso-1 ferricytochrome c is 316 K.…”
Section: Temperature Dependence Of Selected Hyperfine-shifted Proton mentioning
confidence: 99%
See 1 more Smart Citation
“…These data, however, do not agree as well with other studies (Hickey et al, 1988;Das et al, 1989) that place the Tm of this protein near 46 OC. The lower T m may be due to the presence of dimerized protein (Bryant et al, 1985). WT protein, the (+) C102T variant, and the (0) V20C variant at pH 7.2 and 300 K. The curves represent the nonlinear least-squares fits of the data to the two-state hypothesis (Santoro & Bolen, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…a Swint and Robertson, 1993;' O'Neil et al, 1995;Hurle et al, 1990;Viguera et al, 1994; e Jackson et al, 1993;'Akke and Forsen, 1990;Khorasanizadeh et al, 1993;Wintrode et al, 1994;Scholtz, 1995;J Agashe and Udgaonkar, 1995;Lim et al, 1992; ' Marqusee and Sauer, 1994;McLendon and Smith, 1978;Hagihara et al, 1994; O Privalov and Gill, 1988;P Pace et al, 1990;Shirley et al, 1992;Yu et al, 1994; ' Bowie and Sauer, 1989; ' Egan et al, 1993;Ramdas et al, 1986;"Bryant et al, 1985; " Cohen and Pielak, 1994;x Kelley et al, 1987;Santor0 and Bolen, 1992;'Clarke and Fersht, 1993; aa Pace et al, 1992;" Griko et al, 1994; cc Greene and Pace, 1974;dd Munson et al, 1994;Filimonov et al, 1993; f f Saito and Wada, 1983; gg Ahmad and Bigelow, 1982; hh Taniyama et al, 1992; I' Herning et al, 1992;'' Ropson et al, 1990; kk Shortle and Meeker, 1986;"Carra et al, 1994; mm Craig et al, 1987; "" Makhatadze et al, 1994;O0 De Young et al, 1993...…”
Section: Aasamentioning
confidence: 99%